2018
DOI: 10.3171/2016.12.jns161444
|View full text |Cite
|
Sign up to set email alerts
|

Brachyury gene copy number gain and activation of the PI3K/Akt pathway: association with upregulation of oncogenic Brachyury expression in skull base chordoma

Abstract: OBJECTIVE Chordoma is a slow-growing but clinically malignant tumor, and the prognosis remains poor in many cases. There is a strong impetus to develop more effective targeted molecular therapies. On this basis, the authors investigated the potential of Brachyury, a transcription factor involved in notochord development, as a candidate molecular target for the treatment of chordoma. METHODS Brachyury gene copy number and expression levels were evaluated by quantitative polymerase chain reaction in 27 chordoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 35 publications
1
32
0
1
Order By: Relevance
“…Through molecular studies and a highthroughput monotherapy drug screen, we and others have previously shown that the PI3K/AKT/mTOR pathway provides a promising therapeutic target in preclinical models. 6,[9][10][11][12] However, limited response to PI3K inhibition in several of our models suggest the presence of resistance mechanisms prompting the development of combination therapies. Here, we aimed to identify potential synergistic combinations with PI3K pathway inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Through molecular studies and a highthroughput monotherapy drug screen, we and others have previously shown that the PI3K/AKT/mTOR pathway provides a promising therapeutic target in preclinical models. 6,[9][10][11][12] However, limited response to PI3K inhibition in several of our models suggest the presence of resistance mechanisms prompting the development of combination therapies. Here, we aimed to identify potential synergistic combinations with PI3K pathway inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Through targeted exome sequencing and a high-throughput drug screen, our laboratory and others have identified alterations within the PI3 kinase (PI3K)/AKT/mTOR pathway in both chordoma tumors and patient-derived cell lines (including UM-Chor1 and UM-Chor2), and demonstrated the effectiveness of PI3K inhibitor monotherapies in vitro. [6][7][8][9][10][11][12] Subsequent work between our laboratory and the Chordoma Foundation using patient-derived xenograft (PDX) and cell line-derived xenograft (CDX) models showed reduction in tumor growth with PI3K inhibitor, BKM-120 in some, but not all models suggesting that there may be a role for alternative pathways in developing resistance to these drugs. 12,13 In addition to the PI3K signaling pathway, T which encodes the brachyury protein (a nuclear transcription factor responsible for notochord development) is frequently disrupted in chordoma and provides another promising target.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of chordoma cell lines not associated with TSC also revealed a correlation between PI3K/AKT pathway upregulation and brachyury expression ( 66 ). Cells from skull-base chordomas with high brachyury expression had significant upregulation of PI3K/AKT pathway genes compared to low-brachyury tumors ( 66 ). Treatment with PI3K/AKT pathway inhibitors resulted in decreased brachyury expression that corresponded with impaired cell growth ( 66 ).…”
Section: Growth Factor Signalingmentioning
confidence: 99%
“…Otani et al found that brachyury was expressed in all (23) chordomas patients (n=27), albeit with variable levels of expression. Patients with tumors expressing high levels of brachyury were found to have significantly shorter progression free survival compared to those with lower brachyury expression tumors (23). The molecular findings in a chordoma may change how we think about a patient's prognosis.…”
Section: Managementmentioning
confidence: 99%